2020
DOI: 10.3390/ijms21020614
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Role of Nerve Injury-Induced Protein 1 in Myeloid Cells under Intestinal Inflammatory Conditions

Abstract: Nerve injury-induced protein 1 (Ninjurin1, Ninj1) is a cell-surface adhesion molecule that regulates cell migration and attachment. This study demonstrates the increase in Ninj1 protein expression during development of intestinal inflammation. Ninj1-deficient mice exhibited significantly attenuated bodyweight loss, shortening of colon length, intestinal inflammation, and lesser pathological lesions than wild-type mice. Although more severe inflammation and serious lesions are observed in wild-type mice than Ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 55 publications
2
15
0
Order By: Relevance
“… 39 Increased oxidative stress, endoplasmic reticulum (ER) stress (ERS) or NF-κB activation also enhances NINJ1 expression. 40 NINJ1 is involved in many inflammatory diseases, including diabetes mellitus, 24 nervous system inflammatory lesions, 22 intestinal inflammatory conditions, 23 and experimental autoimmune encephalomyelitis. 21 However, these previously established studies on the roles of NINJ1 in inflammation were mainly focused on NINJ1-mediated leukocyte migration, although NINJ1 can also interact with LPS and regulate Toll-like receptor 4 (TLR4) signaling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 39 Increased oxidative stress, endoplasmic reticulum (ER) stress (ERS) or NF-κB activation also enhances NINJ1 expression. 40 NINJ1 is involved in many inflammatory diseases, including diabetes mellitus, 24 nervous system inflammatory lesions, 22 intestinal inflammatory conditions, 23 and experimental autoimmune encephalomyelitis. 21 However, these previously established studies on the roles of NINJ1 in inflammation were mainly focused on NINJ1-mediated leukocyte migration, although NINJ1 can also interact with LPS and regulate Toll-like receptor 4 (TLR4) signaling.…”
Section: Discussionmentioning
confidence: 99%
“… 22 NINJ1 expression results in macrophage activation in intestinal inflammatory conditions. 23 Blocked of NINJ1 protected diabetic endothelial cells from high-glucose induced apoptosis in diabetes mellitus. 24 Besides, NINJ1 asp110ala single nucleotide polymorphism is associated with protection in leprosy nerve damage.…”
Section: Introductionmentioning
confidence: 97%
“…The safety level was measured by evaluating ERK phosphorylation [ 37 ]. Dovitinib (TKI258) is an inhibitor of multiple kinases, including FGFR, VEGFR, and platelet-derived growth factor receptor (PDGFR); its efficacy has been proven in HER2-negative metastatic breast cancer (NCT00958971), and it inhibits the invasion of MDA-MB-231(SA) cells [ 38 , 39 ]. E-3810 inhibits FGFR1 , FGFR2 , CSF1R , VEGFR1 , VEGFR2 , and VEGFR3I [ 40 ].…”
Section: Targets Of Tnbc Under Active Clinical Evaluationmentioning
confidence: 99%
“…To our knowledge, several pieces of research elucidate that abnormal activation of proinflammatory macrophages could lead to intestinal inflammation [34, 35]. Concomitantly, Jung et al [36] proclaimed that Ninj1 expression was significantly enhanced in the dextran sodium sulfate-induced mice intestinal inflammation models, especially on the surface of macrophages. More importantly, Ninj1-knockout mice exhibited mild clinical phenotype and pathological lesions than wild-type (WT) mice during experimental colitis.…”
Section: Roles Of Ninjurin1 Outside the Nervous Systemmentioning
confidence: 99%
“…More importantly, Ninj1-knockout mice exhibited mild clinical phenotype and pathological lesions than wild-type (WT) mice during experimental colitis. Furthermore, Jung et al [36] concluded that Ninj1 contributes to the activation of macrophages, thereby promoting the secretion of proinflammatory factors and chemokines, such as IL-1β, IL-6, and CCL2, via the TLR4-protein Kinase C δ/θ signaling pathway during the development of colitis in vivo [36]. Notably, unlike its role in the CNS, Ninj1 does not promote the infiltration of macrophages into the inflammatory lesion site, but rather promotes the activation of macrophages under the intestinal inflammatory conditions [36].…”
Section: Roles Of Ninjurin1 Outside the Nervous Systemmentioning
confidence: 99%